2010
DOI: 10.1021/ef100556b
|View full text |Cite
|
Sign up to set email alerts
|

Energy Savings and Emission Reduction of Nitrogen Oxides, Particulate Matter, and Polycyclic Aromatic Hydrocarbons by Adding Water-Containing Acetone and Neat Soybean Oil to a Diesel-Fueled Engine Generator

Abstract: Dieselhols (blends of diesels, biodiesels, and alcohols) have received considerable attention because of their low emission of CO2. In this study, new blended fuels were formed by adding 1−3 wt % of water-containing acetone (WA) or dehydrated acetone (AC) into a regular diesel (95−97%) and using 1 wt % of isopropyl alcohol (P) and 1 wt % of neat soybean oil (S) or soybean biodiesel (B) as stabilizers. The blended fuels were tested for their energy efficiencies and pollutant emissions in a diesel-fueled engine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 60 publications
(25 citation statements)
references
References 39 publications
0
24
1
Order By: Relevance
“…Some previous studies indicated that the oxygenated additives in diesel can improve the thermal efficiency of engine and reduce the BSFC (Yoshimoto et al, 1999;Lin et al, 2006;Lin et al, 2010;Mwangi et al, 2015a;Tsai et al, 2015b). However, the alternative ratios in the current study were too high to overcome the loss of heating values.…”
Section: Fuelscontrasting
confidence: 54%
“…Some previous studies indicated that the oxygenated additives in diesel can improve the thermal efficiency of engine and reduce the BSFC (Yoshimoto et al, 1999;Lin et al, 2006;Lin et al, 2010;Mwangi et al, 2015a;Tsai et al, 2015b). However, the alternative ratios in the current study were too high to overcome the loss of heating values.…”
Section: Fuelscontrasting
confidence: 54%
“…Notably, the fuel oxygen content of W40D60 and W60D40 were 5.4 and 7.6, respectively, which were significantly higher than that of D100 (1.0%). The fuel oxygen was reported to improve the oxidation reaction in our previous studies and reduce PM, CO, HC, and PAH emissions (Lin et al, 2010(Lin et al, , 2012Chang et al, , 2014. Additionally, the chlorine, sulfur, and aromatic contents could also affect several emissions, such as PCDD/Fs, PCBs, PCDEs, PAHs, PM, SO 2 , and HCl.…”
Section: Chemical Compositionsmentioning
confidence: 93%
“…One of these is the dilution effect that reduces the PAHs present in the overall combusted fuel (Lin et al, 2006a(Lin et al, , 2008Lin et al, 2010;Lee et al, 2011;Chang et al, 2013;. Furthermore, the addition of water causes the micro-explosion phenomena resulting in more turbulent combustion environment that enhances the air/fuel mixing.…”
Section: Polycyclic Aromatic Hydrocarbons (Pahs)mentioning
confidence: 99%
“…According to (Alahmer, 2013) various ways of incorporating water in the combustion process include use of separate injectors for water and diesel, fumigation in the air intake system, mixing the fuel and water in the fuel lines prior to injection or forming emulsions. The use of water-fuel emulsions have led to remarkable reduction in pollutant emissions especially achieving NO x -PM trade-offs (Lin et al, 2010;Subramanian, 2011;Alahmer, 2013;Chang et al, 2014b). Water emulsions result in micro-explosion phenomena, whereby during combustion, water evaporates faster than diesel due to differences in boiling points (Hagos et al, 2011).…”
Section: Introductionmentioning
confidence: 99%